Кінетика видалення газів з металевого розплаву під час дегазації на обладнанні камерного типу - Піптюк, В.П.; Самохвалов, С.Є.; Логозинський, І.М.; Греков, С.В.; Красніков, К.С. (Physico-technological Institute of Metals and Alloys, 2023)
The main purpose of liquid metal degassing is to ensure a low content of gases (hydrogen, nitrogen) in steel. First of all, this applies to flocks-sensitive steel grades and reducing the content of non-metallic inclusions for steel of those grades from which wire and other metal products with small cross-section and high quality requirements are made. The parameters of this promising direction of out-of-furnace processing influence the processes of metal degassing, and the study of their influence is relevant and has practical and scientific interest. Previously, with the help of the developed software product, the processes of melt mixing and its thermal state during degassing in a steel ladle with a capacity of 60 tons with reinforced of lining gain in impact zone on specialized chamber equipment in the conditions of PJSC "DSS" were numerically investigated. The kinetics of hydrogen and nitrogen removal during degassing were studied according to contour diagrams with the same initial (certain gas content, fixed metal mass, constant properties of reacting phases, etc.) and different technological ones (argon consumption, processing time, change of bucket filling level with metal, etc.) parameters. The influence of variable factors on the efficiency of removal of dissolved gases at reduced pressure (1 mm Hg) above the melt surface was evaluated. The average content of hydrogen and nitrogen in the ladle bath was compared with the corresponding content of these gases in a separate place on the metal surface, which corresponded to the specified place of sampling of the metal during degassing. Additionally, the content of argon in the metal consumed for its mixing during vacuum treatment was determined. Based on the results of numerous studies, sufficient argon consumption was required to purge the bucket bath with different (within practical fluctuations) metal mass and determined the minimum possible duration of the degassing process on this type of equipment in PJSC "DSS", which provide the required gas content. In order to verify the theoretically obtained results in the conditions of PJSC "DSS" experimental and industrial experiments were initiated.